Ambient Vibration Measurements of the Bosphorus Suspension Bridge by Total Station and GPS - Erdogan, H.; Gulal, E. (WILEY-BLACKWELL, 2013)
Traffic and wind excitations have been used to obtain the dynamic characteristics of the Bosphorus Suspension Bridge in Istanbul, Turkey. Ambient vibration measurements (AVMs) on the bridge deck were obtained using the Total Station (TS) in 2003 and the Global Positioning System (GPS) in 2005. Frequencies can be effectively estimated from AVMs using the peak-peaking (PP) method in the frequency domain. For the main span, seven vertical and seven lateral frequencies were obtained from TS measurements. From the GPS measurements, 13 vertical and 9 lateral frequencies were obtained. All 36 frequencies were in the range 01.5 Hz. Estimated frequencies from the measurements and three-dimensional finite-element (FE) models were compared. In general, the agreement among frequencies was good. Comparison with frequencies from more limited studies undertaken in 1973, 2003, and 2005 showed that there was no unexpected behaviour in the movements of the bridge and the bridge continues to behave in accordance with the original design specifications.
Keywords: Bosphorus Suspension Bridge; Ambient Vibration Measurements; Average Normalized Power Spectral Density; Peak-Peaking; Finite-Element Method; CABLE-STAYED BRIDGE; Engineering; Mechanics; Materials Science